Pengaruh Budaya Kerja dalam Organisasi terhadap Kepuasan Kerja Guru di Sekolah-sekolah Menengah Daerah Hulu Perak - Nor Aroma Abu Bakar; Khairul Zaidy Mansor; Nor Zorrenee Zokarphy (Neolectura, 2022)
A quantitative study that aims to look at the level of teacher job satisfaction and its relationship to the work culture that is practiced in secondary schools. A total of 305 teachers serving in secondary schools in the Hulu Kinta area have been involved in this study. The inquiry form related to teacher job satisfaction was used to collect the desired data and analyzed with the help of the Statistical Program for Social Science (SPSS) version 23.0. The results of the study found that the teacher's job satisfaction stage was at a simple stage with a min score between ±3.34 to ±4.27. This study also shows that there are differences in the stages of job satisfaction between gender and age variables (F = 2.735, p = 0.044), education stage (F = 2.679, p = 0.047) while marital status factors (t = -.856 and p value = 0.392 ) and work experience (F= 2.014; p=0.112) also showed no difference in teacher job satisfaction. However, this study concludes that there is no difference between school bands and work culture among teachers who work in secondary schools in the Hulu Kinta Perak area except in the aspect of 'communication style' with a p value of .022. This study found that work culture factors in the 'guarding' aspect and the 'innovation' and 'taking risks' aspects were the most significant predictors of work culture that influenced the job satisfaction of the sample teachers of this study. Therefore, several suggestions have been suggested, such as the awareness of the management to improve the practice of a more positive work culture, interventions to increase the motivation and virtue of teachers. The role of students, parents and the community is also important as an effort to help the school achieve a high level of job satisfaction and then help students' academic brilliance and school success.